Fatwa DSN-MUI Tentang Pedoman Penjaminan Simpanan Nasabah Bank Syariah Perpsektif Sadd Adż-Dżarī’Ah - Mahmudi, Muh; Fathudin, Fathudin; Riyanto, Septian Viktor (CV. ULIL ALBAB CORP, 2024)
This study discusses the deposit insurance of Islamic bank customers using the sadd dzari’ah approach in the DSN-MUI fatwa. The use of sadd dzari’ah aims to prevent losses and uncertainty in Islamic banking practices. This research employs a library research method with a philosophical-normative approach, examining related literature and the implementation of the fatwa. DSN-MUI Fatwa No.118/DSN-MUI/II/2018 establishes deposit insurance regulations based on the principle of kafalah, where the Indonesia Deposit Insurance Corporation (LPS) acts as the guarantor and the customers as the insured parties. The implementation of sadd dzari’ah is evident in LPS’s authority to reject claims that do not meet the criteria, adjust premiums based on risk, separate the management of Islamic and conventional funds, and establish transparency and accountability provisions. The study finds that DSN-MUI Fatwa No.118/DSN-MUI/II/2018 implements the sadd dzari’ah principle to prevent losses and maintain the integrity of Islamic banking. LPS can reject claims that do not meet sharia criteria, adjust premiums based on risk, and separate the management of Islamic bank funds. Investments in sharia-compliant financial instruments and claim arrangements consider customer obligations to ensure fairness. These provisions ensure financial stability and protect customers in accordance with sharia principles.